Moderation Study In the Influence of Neurotransmitters on Investment Bias in Female Investors in Indonesia - Lena Lestary; Nugraha Nugraha; Maya Sari; Disman Disman; Erik SA (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to meticulously explore the moderating effect of financial literacy on the influence of neurotransmitters on investment bias. As a pioneering effort in behavioral finance, this research highlights cognitive and psychological aspects of investors, focusing specifically on female investors, and represents the first study to integrate financial literacy as a moderating variable in the context of neurotransmitter effects. Methodology: A quantitative approach was employed, targeting female stock investors in Indonesia. Purposive sampling was used alongside a semantic differential scale. Data were collected through the distribution of closed-ended questionnaires, preceded by instrument testing and a pre-survey. A total of 581 respondents participated, and data were analyzed using Structural Equation Modeling (SEM) Main Findings: The main findings reveal that financial literacy negatively affects investment bias, indicating that greater financial knowledge tends to reduce behavioral bias. However, even financially literate individuals may still exhibit bias. Furthermore, neurotransmitter activity shows a significant positive effect on investment bias, suggesting that biological factors amplify biased decision-making. Importantly, financial literacy significantly moderates this relationship in a negative direction, meaning that higher levels of financial understanding weaken the influence of neurotransmitters on investment bias. Novelty/Originality of this study: This research contributes novel insights to the development of behavioral finance theory by introducing financial literacy as a moderating factor in the biological–psychological pathway influencing investment behavior. The practical implications highlight the critical role of financial education in reducing behavioral biases in investment decision-making, especially among female investors.